Telehealth Model Strategy to Improve Maternal Feeding Practices in Children with Stunting: Randomized Control Trial - Yolanda, Henny; Mardani, Raden Ahmad Dedy; Supinganto, Agus (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: The eating behaviour of the stunted children is the high risk for their growth and development. Given the urgency of all the impacts caused and its high prevalence, handling stunting through changes in feeding patterns requires serious attention from the government, society, and individuals as a whole. This study utilises telehealth as an innovative solution to overcome the challenges in feeding children with stunting. The aim of this study is to improve maternal feeding practices for children with stunting using telehealth. Methods: This study uses the single-blind randomised controlled trial method. The sampling method in this study was by using purposive sampling. The participants of this study are 41 mothers who have a child with stunting. Results: There was a significant effect (p=0.169) of the Telehealth Model Strategy to Improve Maternal Feeding Practices in Children with Stunting. Conclusion: We found that the telehealth model can be used to improve maternal feeding practices for children with stunting using telehealth.